Sunshine foaming of compact Ti3C2Tx MXene film for highly efficient electromagnetic interference shielding and energy storage. (September 2021) - Yin, Liang; Kang, Hui; Ma, Haoxiang; Wang, Jingfeng; Liu, Yuyan; Xie, Zhimin; Wang, Youshan; Fan, Zhimin
Abstract: The controllable construction of lightweight, highly conductive, porous and flexible Ti3 C2 T x MXene film is crucial in achieving high-performance electromagnetic interference (EMI) shielding and the next generation of high-rate energy storage materials, but it is difficult to produce. Herein, the focused sunlight was used to stimulate the photothermal effect of MXene, which makes the free water between the layers of the conventional compact MXene film vaporized instantaneously, and then a macroporous MXene film with 3D architectures was obtained in just a few seconds. Such macroporous MXene film is lightweight and flexible, with high conductivity (≈1000 S cm −1 ), good hydrophobicity and environmental stability. Therefore, the absolute shielding effectiveness of the macroporous MXene film can be as high as 88333 dB cm 2 g −1, indicating its potential applications in EMI shielding materials for aerospace. Furthermore, based on the highly open pore structure and more exposed surface area, this MXene film possesses a higher capacitance (380 F g −1 ) and good rate capability, enabling it to demonstrate attractive prospects in high-rate energy storage. This work provides an ingenious way to create macroporous MXene film and can guide future work on exploring the wider use of MXene-based materials. Graphical abstract: Image 1